How Social Media Information Affects the Intention to Uptake Covid-19 Vaccine: Integrating ELM and HBM Models - Zhang, Yundi; Jin, Xin; Yan, Lihan (The 72nd International Communication Association Annual Conference, 2022)
Combining the elaboration likelihood model and health belief model, this study proposed an integrative model and confirmed the peripheral route (perceived opinion climate) as the main effect on audiences’ intention to uptake the COVID-19 vaccine. The main finding is that a main effect of perceived opinion climate on perceived benefit, perceived barrier, and intention to vaccinate was found. Details are as follows